PROSES DIFUSI INOVASI IDENTITAS KEPENDUDUKAN DIGITAL (IKD) DI KABUPATEN BOYOLALI - Putri Oktaviana, Prita Veronica; Warsono, Hardi; Astuti, Retno Sunu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
In the era of digitalization, technological and information developments are increasingly developing. The government has made a new breakthrough in the field of population administration through the innovation of Digital Population Identity (IKD). The aim of the IKD is to facilitate and speed up public service transactions in digital form. The process of diffusion of this innovation is important in ensuring its acceptance and successful implementation in society. This research aims to analyze the process of diffusion of Digital Population Identity (IKD) innovation in Boyolali Regency as well as the obstacles in the process of diffusion of Digital Population Identity (IKD) innovation in Boyolali Regency. This research uses a qualitative descriptive approach with data collection techniques through observation, interviews and documentation and uses Rogers' theory. The research results show that the process of diffusion of Digital Population Identity (IKD) innovation in Boyolali Regency through stages consisting of knowledge, persuasion, decision making, implementation and confirmation has become the focus in efforts to spread this innovation. However, even though they have passed these stages, the IKD innovation diffusion process in Boyolali Regency has still not reached its maximum level. However, this diffusion process does not run without obstacles. Psychological barriers include low levels of trust, concerns about data security, and negative experiences that influence people's attitudes and interest towards IKD. Meanwhile, practical obstacles include limited human resources in dissemination, lack of technological literacy, difficulty in using the application, and complicated requirements. This obstacle shows that even though it has gone through various stages, further efforts are still needed to increase the effectiveness and acceptance of IKD innovation in the Boyolali Regency community.